A COMPARATIVE STUDY ABOUT PERCEPTIONS OF TEACHING METHODS AMONG UNIVERSITY STUDENTS IN FINLAND AND GERMANY : A CASE STUDY OF THE UNIVERSITY OF TURKU AND THE UNIVERSITY OF REGENSBURG - Oyedayo, Oyeleye (My University, 2019)
The present study investigated students’ perceptions about teaching methods in the University of Turku (UTU), Finland and the University of Regensburg (UR), Germany. The objective was to investigate the differences and similarities between their perceptions. Most previous studies focused on university teachers’, not students’ perceptions, about teaching methods. The purpose of the study was to investigate whether discrepancies existed between students’ perceptions and literature. Data was collected by administering 220 questionnaires to the bachelor’s and master’s degree Education students, using a convenience sampling technique. In total, 216 were retrieved, while 199 were valid for the study, where 87 (44%) and 112 (56%) were from UTU and UR, respectively. Quantitative research design was adopted. The reliability of the instrument was determined, using cronbach alpha coefficient for student-centred method scale (r=.74), teacher-centred method scale (r=.64) and teacher-student interactive method scale (r=.80). The data was grouped, using factor analysis. Descriptive statistics of frequency counts and simple percentage was used for the demographic data section. Ttest was used to analyze the similarities and differences between students’ perceptions, for other sections addressing the three teaching methods. Based on students’ perceptions, their teachers predominantly used student-centred method, occasionally used teachercentred method, but slightly disagreed that they used teacher-student interactive method. Additionally, using .05 significant level, there was significant difference between their perceptions about teacher-centred method (p=.01), while student-centred (p=.13) and teacher-student centred methods (p=.86) recorded no significant difference.
Keywords: Comparative case study, Teaching methods, University teachers, University students, Germany, Finland